Reductions in incident coronary heart disease risk above guideline physical activity levels in men - Williams, Paul T. (2009)
BACKGROUND: One-half of Americans currently meet guideline physical activity levels. For these individuals, exceeding guideline levels may provide additional health benefits. METHODS: Incident physician-diagnosed myocardial infarction and angina, revascularization procedures (CABG, PTCA), and ischemic heart disease deaths during 7.7-year follow-up were compared to baseline usual distance run in 35,402 male runners. RESULTS: Men reported 467 incident CHD and the National Death Index identified an additional 54 ischemic heart disease deaths. Per km/day run, the men’s risks declined 5% for fatal and nonfatal CHD (P = 0.001), nonfatal CHD (P = 0.0008), and revascularization procedures (P = 0.002). Their risks for nonfatal myocardial infarctions and angina declined 7% (P = 0.02) and 10% (P = 0.003), respectively. Compared to <3 km/day run (upper limit guideline level), >9 km/day run produced risks 65% lower for angina (P = 0.008), 29% lower for nonfatal CHD (P = 0.04), and 26% lower for fatal and nonfatal CHD (P = 0.06). CONCLUSIONS: Exceeding guideline physical activity levels produce important CHD-risk reductions.